2015
DOI: 10.4071/isom-2015-tha14
|View full text |Cite
|
Sign up to set email alerts
|

Two step silicon microfluidics for capillary valve applications

Abstract: In this publication, we report on a robust and scalable process flow for fabrication of valves, compatible with other microfluidic components using silicon microfabrication techniques. The valves require an abrupt change in both the depth and width of a rectangular microchannel for proper functioning. We report on the process that allow for a very sharp interface between the two areas of the channel. A non-sharp interface will results in leaky valves. We show the variation in silicon etch depth as function of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…by a 200 nm layer of thermal oxide grown on the silicon surfaces. More details about the fabrication procedure can be found in Majeed et al (2015) . The test devices were fabricated as open surface microchannels.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…by a 200 nm layer of thermal oxide grown on the silicon surfaces. More details about the fabrication procedure can be found in Majeed et al (2015) . The test devices were fabricated as open surface microchannels.…”
Section: Methodsmentioning
confidence: 99%
“…A second channel, usually at a right angle to the direction of propagation of the stopped fluid, is used to convey another fluid stream that meets with the stopped liquid-vapor interface to trigger or re-start the flow of the stopped fluid. Several different designs and methods of fabrication of capillary trigger valves have been proposed over the past several years ( Zimmermann et al, 2008;Hitzbleck et al, 2012;Safavieh and Juncker, 2013;Majeed et al, 2015 ). Most recently, reliable capillary trigger valves have been reported using a two-depth structure and a hydrophobic cover ( Safavieh and Juncker, 2013;Majeed et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fabrication process consists of three silicon deep reactive ion etch steps, one anodic bonding and one metal etching steps. The micro-channels and bubble chamber are fabricated by a shallow, 30 μm etch from one side of silicon surface and a deeper, 200 μm etch defines liquid reservoirs and the stop valve openings using a process flow similarly reported by Majeed et al (2015). Next, these structures are sealed by anodic bonding to a Pyrex wafer.…”
Section: Fabricationmentioning
confidence: 99%
“…No valve failures were reported with 50 experiments conducted. Majeed et al (2015) reported a fabrication process for two-step trigger valves in silicon. Although the valve reliability improves markedly compared to the planar trigger valve, the drawback to these two-level designs is an increase in complexity of the manufacturing process.…”
Section: Introductionmentioning
confidence: 99%